1991
DOI: 10.1111/j.1600-9657.1991.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the penetration of a root canal filling material into the mandibular canal. I. Tissue reaction to the material

Abstract: The root canal filling paste Vitapex (Neo Dental Chemical Products Co., Tokyo), made of calcium hydroxide and iodoform with the addition of silicone oil, was experimentally introduced into the mandibular canals of 29 dogs. Tissue reactions to the paste were examined by radiography, histopathology, and electron microscopy. These examinations revealed that the paste was phagocytosed by macrophages and, in general, was gradually resorbed over time. The paste was also found to cause heterotopic calcification and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…In an experimental study on dog and monkey teeth, Sealapex was found to encourage apical closure by cementum deposition compared with Kerr Root Canal Sealer (SybronEndo/Kerr) when the root filling was 1 mm short of radiographic apex (47). Vitapex introduced into the mandibular canal of dogs caused heterotopic calcification and ossification within the area of penetration (48). Others found no significant differences in periapical tissue responses between Sealapex, CRCS, and a ZOE-based sealer in dog teeth (33).…”
Section: The Effect Of Calcium Hydroxide On Periapical Tissue Healingmentioning
confidence: 96%
“…In an experimental study on dog and monkey teeth, Sealapex was found to encourage apical closure by cementum deposition compared with Kerr Root Canal Sealer (SybronEndo/Kerr) when the root filling was 1 mm short of radiographic apex (47). Vitapex introduced into the mandibular canal of dogs caused heterotopic calcification and ossification within the area of penetration (48). Others found no significant differences in periapical tissue responses between Sealapex, CRCS, and a ZOE-based sealer in dog teeth (33).…”
Section: The Effect Of Calcium Hydroxide On Periapical Tissue Healingmentioning
confidence: 96%
“…Kawakami et al did histopathological studies regarding tissue reactions to calcium hydroxide-based root canal filling material [5][6][7][8] . We also previously reported and discussed in detail the tissue damage and its fate in vivo [9][10][11][12] . The data presented by Kawakami et al in 2012 were published as a monographs 12) .…”
Section: Discussionmentioning
confidence: 99%
“…[10,11,12] Calcium Hydroxide from the pulpecotmy material can also cause heterotopic calcifications in the body tissues. [13] With regards to all these aspects, this combination of material may not ideal and safe.…”
Section: Discussionmentioning
confidence: 99%